Conveying value via categories - Paula Onuchic; Debraj Ray (Theoretical Economics, 2023)
A sender sells an object of unknown quality to a receiver who pays his expected value for it. Sender and receiver might hold different priors over quality. The sender commits to a monotone categorization of quality. We characterize the sender's optimal monotone categorization, the optimality of full pooling or full separation, and make precise a sense in which pooling is dominant relative to separation. As an application, we study the design of a grading scheme by an educational institution which seeks to signal student qualities and simultaneously incentivize students to learn. We show how these incentive constraints are embedded as a distortion of the school's prior over student qualities, generating a monotone categorization problem with distinct sender and receiver priors.
Keywords: D82; D83; 330; heterogeneous priors; information design; Monotonic categorization